Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan PT. Rezeki Famili Terpadu Medan - Citra, Mutiara; Syafrizal, Syafrizal; Yudha, Tri Kartika (Universitas Islam Islam Sumatera Utara, 2023)
The formulation of the problem in this study is how compensation affects employee performance. How does motivation affect employee performance. How compensation and motivation affect employee performance. The purpose of this study is to determine and analyze the effect of compensation on employee performance. To know and analyze the effect of motivation on employee performance. To know and analyze the effect of compensation and motivation on employee performance. The sample in this study amounted to 37 employees. Data analysis techniques in this study used descriptive analysis and multiple linear regression analysis. The results of this study explain that compensation variables have a positive and significant effect on employee performance. Motivation variables have a positive and significant effect on employee performance. Compensation and motivation variables have a positive and significant effect on employee performance.